Neuroprotective effects of docosahexaenoic acid on hippocampal cell death and learning and memory impairments in a valproic acid‐induced rat autism model. Issue 49 (27th November 2015) - Gao, Jingquan; Wang, Xuelai; Sun, Hongli; Cao, Yonggang; Liang, Shuang; Wang, Han; Wang, Yanming; Yang, Feng; Zhang, Fengyu; Wu, Lijie
Abstract: Prenatal exposure to valproic acid (VPA) in rat offspring is capable of inducing experimental autism with neurobehavioral aberrations. This study investigated the effect of docosahexaenoic acid (DHA) on hippocampal cell death, learning and memory alteration in an experimental rat autism model. We found that DHA supplementation (75, 150 or 300 mg/kg/day, 21 days) rescued the VPA (600 mg/kg) induced DHA reduction in plasma and hippocampus in a dose‐dependent manner, increased the levels of hippocampal p‐CaMKII and p‐CREB without affecting total protein level, and altered BDNF‐AKT‐Bcl‐2 signaling pathway, as well as inhibited the activity of caspase‐3. DHA also influenced the content of malondialdehyde (MDA) and the activities of antioxidant enzymes in the VPA‐treated offspring. Consistent with the previous results, we also observed that 300 mg/kg DHA supplementation markedly increased the cell survival, decreased the cell apoptosis, and increased mature neuronal cell in the hippocampus in VPA‐treated offspring. Utilizing the Morris water maze test, we found that DHA prevented cognitive impairment in offspring of VPA‐treated rats. The data suggested that DHA may play a neuroprotective role in hippocampal neuronal cell and ameliorates dysfunctions in learning and memory in this rat autism model. Thus, DHA could be used as treatment intervention for mitigating behavioral dysfunctions in autism spectrum disorder (ASD).